Legal Protection of Go-Jek Driver That Experiences Damages Due To The Fictive Order In Go-Food Menu In Go-Jek Aplication - Hermawan, Aditya; Susanti, Erna; Hidayatullah, Syukri (Faculty of Law, Mulawarman University, 2018)
This research is proposed to answer two questions: Firstly, to find out the cause of fictitious orders experienced by Go-Jek drivers in the Go-food menu in Go-Jek app. Secondly, to know the legal protection of Go-Jek drivers who suffered losses due to a fictitious plane in the Go-food menu on the Go-Jek app. And the research is directed to educate the public the importance of Civil law which governs agreement in the life of society. This study uses socio-legal approach with a number of resource persons. The choice of approach to socio-legal does not mean disregarding doctrinal side support on the grounds that one of the aims of this study sees a set of positive norms in relation to Legal protection of Go-Jek drivers, including legal theory support with a view to verifying the implementation of law in practice (protection and responsible). This study concludes that, Transactions using Go-Jek access has so far caused legal consequences among others who is responsible for the losses experienced by drivers, whether the Go-Jek party is responsible for the losses experienced drivers, including what kind of legal protection obtained by the driver when suffering application losses by irresponsible consumers. The factors of the emergence of fictitious orders are the existence of competitions between the Go-Jek driver, Go-Jek verification system is still weak, and the existence of bad faith in someone. Partnership agreement between PT. Go-Jek and Go-Jek’s driver is a standard clause that created and provided without involving the Go-Jek drivers in which there is a clause of transfer of responsibility because of PT. Go-Jek as the Go-Jek application service manager will not be responsible if there is a loss caused by the use of Go-Jek application. The legal relations and responsibilities of the parties should be clearly stipulated in the partnership agreement between PT. Go-Jek Indonesia, and Partners are created based on mutual agreement and agreement between both parties. To minimize the losses experienced by Go-Jek drivers in service delivery for every use of consumer spending service must have a Go-Pay account, which expenditures can not be executed if the balance in the Go-Pay account is insufficient to make an expense transaction.